The Impact of Social Capital on the Education of Migrant Children. (2nd September 2013) - Salinas, José P.
Abstract : This study used a life‐history qualitative research design to explore social capital within migrant families to understand the impact of social capital on the education of migrant children. The study specifically examined the family culture and the educational experiences of six adult Latinos and/or Latinas who as children followed the migrant stream with their parents to obtain temporary agricultural work. The findings illustrate how social capital was beneficial for student performance in and out of the classroom through intersecting themes and patterns which included consejos, familismo, and compadrazgo. Culturally based recommendations for school leaders and community organizations are presented.